THE IMPACT OF KINDERGARTEN HEAD’S MANAGERIAL COMPETENCY ON IMPROVING PRESCHOOL EDUCATIONAL QUALITY - Widiastuty, Yessy; Muji Gunarto (Dinasti International Journal of Digital Business Management, 2020)
The purpose of this study is to examine the impact of managerial competency on improving education quality in preschool education. When the kindergarten head has managerial competency, she is able to manage, regulate and move the educational institution to the maximum in achieving the institution’s targets and ideals stated in the vision and mission of the institution with high and measurable quality of education. This research survey was conducted in one sub-district in Palembang city, Indonesia. The samples were 131 kindergarten heads, teachers and administrative staff from 12 kindergartens in Ilir Barat 1 district Palembang city. The sampling technique used is random and the data analysis used is structural equation modelling (SEM) analysis. The results show that the managerial competency of the kindergarten head has a positive and significant impact on improving the preschool educational quality , as well as improving the image of the institution in the community.